Channel estimation for spatial modulation orthogonal frequency division multiplexing systems - Doğan, Hakan; Panayırcı, Erdal; ACAR, YUSUF (IEEE, 345 E 47th St, New York, Ny 10017 USA, 2015)
A combination of spatial modulation and orthogonal frequency division multiplexing (SM-OFDM) has been recently proposed for multicarrier systems while assuming the perfect channel state information (P-CSI) available at the receiver. But, in practical scenarios, the estimation of CSI is crucial in order to detect the transmitted data coherently. In this work(1), a new frame structure and pilot symbol aided channel estimation (PSA-CE) technique with a piecewise linear interpolation is proposed for the SM-OFDM systems operating in the presence of frequency selective channel. Bit error rate (BER) performance of the proposed channel estimation technique is then investigated with different channel models such as Typical Urban ( TU) and Rural Urban (RU) for 4-quadrature amplitude modulation (QAM). In particular, it is shown that the performance with estimated channel came close to that with known channel within 2.3 dB in SNR for BER = 10(-4) for TU channels.
Keywords: multiple-input multiple-output (MIMO); orthogonal frequency division multi- plexing (OFDM); spatial modulation (SM); channel estimation; interpolation